Multi-Dimensional Values on Customers' Intention to Revisit Green Resorts: The Cultural Case in Malaysia - Nor Rabiatul Adawiyah Nor Azam; Basri Rashid; Noor Azimin Zainol; Maliani Mohamad (Journal of Innovation in Educational and Cultural Research, 2020)
This study investigates the concept of perceived value on the customers' intention to revisit Malaysian green resorts. It is a cultural case that happened in Malaysia. The perceived value would be assessed in a formative manner based on a multi-dimensional scale, which includes the dimensions of functional, social, emotional, and epistemic. This research was applied to a survey method. The unit of analysis is the resort customers, with distributed questionnaires to customers who have stayed in one of the selected green resorts and have consumed the products and services at these resorts for at least two days. This study provides significant insights and pertinent recommendations to the hospitality industry and extends the existing body of knowledge by assessing perceived value as an integrated formative construct and examining customers' overall perceived value towards green resorts. This study provides an in-depth understanding of the importance of green resorts associated with the communities, groups, and individuals from one generation to the next. Also, this study can be a benchmark, provide guidance, and the basis for future directions of future studies that are similar. It can contribute to providing a broader perspective on the issue. This study also addresses what academicians can do to teach students in the field of hospitality and tourism, create awareness among individual consumers and finally, to promote sustainability for tourists, travelers, as well participants in the field of hospitality. Next, attention is also given to the teaching of the hospitality and tourism areas in the lodging, meetings and events, and foodservice segments of the industry. Sustainability education in lodging operations includes ensuring that students understand that "green" lodging professionals participate. The paper estimates the demand for customers' intention to revisit the green resort in Malaysia. The originality of this paper comes out to the need to identify the application of green initiatives in the hospitality industry continues to rise in their contribution to preserve the environment as well as meeting the demands of environmentally-conscious customers.